Understanding yeast shells: structure, properties and applications - Larissa Silva de Macêdo; Samara Sousa de Pinho; Anna Jéssica Duarte Silva; Ingrid Andrêssa de Moura; Benigno Cristofer Flores Espinoza; Maria da Conceição Viana Invenção; Pedro Vinícius Silva Novis; Marco Antonio Turiah Machado da Gama; Matheus do Nascimento Carvalho; Lígia Rosa Sales Leal; Bruna Isabel Santos Cruz; Beatriz Mendonça Alves Bandeira; et al. (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: The employment of yeasts for biomedical purposes has become increasingly frequent for the delivery of prophylactic and therapeutic products. Its structural components, such as β-glucans, mannan, and chitin, can be explored as immunostimulators that show safety and low toxicity. Besides, this system minimizes antigen degradation after administration, facilitating the delivery to the target cells. Review approach: This review sought to present molecules derived from yeast, called yeast shells (YS), and their applications as carrier vehicles for drugs, proteins, and nucleic acids for immunotherapy purposes. Furthermore, due to the diversity of information regarding the production and immunostimulation of these compounds, a survey of the protocols and immune response profiles generated was presented. Key results: The use of YS has allowed the development of strategies that combine efficiency and effectiveness in antigen delivery. The capsular structure can be recognized and phagocytized by dendritic cells and macrophages. In addition, the combination with different molecules, such as nanoparticles or even additional adjuvants, improves the cargo loading, enhancing the system. Activation by specific immune pathways can also be achieved by different administration routes. Conclusion: Yeast derivatives combined in different ways can increase immunostimulation, enhancing the delivery of medicines and vaccine antigens. These aspects, combined with the simplicity of the production steps, make these strategies more accessible to be applied in the prevention and treatment of various diseases.